The mechanism for bacteriophage f2 removal by nanoscale zero-valent iron. (15th November 2016) - Cheng, Rong; Li, Guanqing; Shi, Lei; Xue, Xingyan; Kang, Mi; Zheng, Xiang
Abstract: Nanoscale zero-valent iron (NZVI) has shown excellent performance for pathogenic microorganism removal but the inactivation mechanism has not been understood clearly enough. In this study, the bacteriophage f2 removal by NZVI under aerobic and anaerobic conditions was investigated, and various factors involved in f2 removal were analyzed in detail, including the ion products of NZVI (Fe(II), Fe(III)), solid phase products, the reactive oxygen species (ROS), O2 and H + . In addition, the morphologies of bacteriophage f2 during reaction were observed. The results showed that the removal efficiency of bacteriophage f2 was much higher under aerobic conditions than that in anaerobic systems, and oxygen and pH were determinants for f2 removal. The oxidation of Fe(II) was a fundamental step and played a significant role in bacteriophage f2 removal, especially in the aerobic systems. In the presence of oxygen, the virus removal was attributed to the generation of ROS (namely ·OH and ·O2 − ) and the oxidized iron, in which the ROS (·OH and ·O2 − ) made a predominant contribution. And the adsorption of iron oxide was responsible for the removal in oxygen depleted circumstance. In the anaerobic system, the virus removal was mainly attributed to the interaction between NZVI and bacteriophage f2. Besides, from the perspective of TEM images, the virus removal was mainly attributed to the damage of infective ability by NZVI at the initial stage of reaction, and later the virus was inactivated by the ROS generated. Graphical abstract: Highlights: The removal efficiency of phage f2 by NZVI was much higher in aerobic conditions. Oxygen and pH of solution were determinants for bacteriophage f2 inactivation. The oxidation of Fe(II) was a fundamental step and played a significant role. In aerobic system, the ROS (namely ·OH and ·O2 − ) made a predominant contribution. In anaerobic system, the interaction between NZVI and phage f2 was the main reason.